2021
DOI: 10.1097/md.0000000000026354
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and systemic immune inflammation index in acute ischemic stroke

Abstract: The acute ischemic stroke (AIS) is a devastating disease and remains the leading cause of death and disability. This study aims to evaluate the role of hematological inflammatory markers (neutrophil-to-lymphocyte ratio [NLR], platelet-to-lymphocyte ratio [PLR], and systemic immune inflammation index [SII]) in predicting the neurological recovery in acute cerebrovascular events over 1-year follow-up. Adult patients diagnosed with AIS within 3 hours from January 2016 to December 2018 were recruited re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
(80 reference statements)
1
21
0
Order By: Relevance
“…Previous studies demonstrated that the complete blood count parameters and the ratio between them might act as markers for prognosis, status, and progression of diseases (20,21). PLR was reported to be closely related to the progression and prognosis of acute ischemic stroke, knee osteoarthritis, and papilledema due to idiopathic intracranial hypertension (22,23). AS is a chronic inflammatory autoimmune disease, and we aimed to determine the relationship between AS and PLR.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies demonstrated that the complete blood count parameters and the ratio between them might act as markers for prognosis, status, and progression of diseases (20,21). PLR was reported to be closely related to the progression and prognosis of acute ischemic stroke, knee osteoarthritis, and papilledema due to idiopathic intracranial hypertension (22,23). AS is a chronic inflammatory autoimmune disease, and we aimed to determine the relationship between AS and PLR.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that SII is a potential indicator for clinical endpoints for patients with coronary artery disease (13,14). The same was found in patients with hypertension (15), acute ischemic stroke (17), and chronic HF (27). However, no previous study has discussed the predictive value of SII in HCM.…”
Section: Discussionmentioning
confidence: 86%
“…Also, several studies indicated that markers of inflammation predicted adverse outcomes in HCM, such as high-sensitivity C reactive protein (CRP) ( 7 ), monocyte to high density lipoprotein cholesterol ratio (M/HDL-C) ( 8 ), and neutrophil to lymphocyte ratio (NLR) ( 10 ). A novel immune and inflammation index, namely, systemic immune-inflammation index (SII), which is calculated from platelet, neutrophil, and lymphocyte counts, has been examined as a prognostic factor for clinical outcomes in cancer patients ( 11 12 ) and in patients with cardiovascular diseases, such as coronary artery disease ( 13 14 ), hypertension ( 15 ), pulmonary embolism ( 16 ), and acute ischemic stroke ( 17 ). However, to date, the predictive ability of SII for mortality has not been reported in HCM.…”
Section: Introductionmentioning
confidence: 99%
“…In stroke, a retrospective study showed no difference in SII values upon admission between acute IS patients with neurological recovery and acute IS patients with no improvement at 1, 3, 6, and 12 months poststroke [ 59 ]. Conversely, in patients with large artery occlusion, decreased SII was associated with favorable clinical outcomes after MT [ 60 ].…”
Section: Resultsmentioning
confidence: 99%